PENINGKATAN AKTIVITAS PEMBELAJARAN BAHASA INGGRIS MELALUI STRATEGI SAVI (SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUALY) DENGAN MEDIA GAMBAR TERHADAP SISWA KELAS IV SD NEGERI 1 SONOREJO BLORA - Kaltsum, Honest Ummi; Wijayanti, Noviana (Jurnal VARIDIKA, 2012)
This research aims to enhance the activity of learning English, and motivated by the low learning motivation of students at the fourth grade SDN 1 Sonorejo Blora (24 students). The method of data collection is in the form of tests, observation, documentation. Beside, this research applies interactive analysis to analyze the data collected. The results of this research show that there is an enhancement in the 1. Asking activity: first cycle 33.3%, 41.6% the second cycle, the third cycle of 50%; 2. Expressing their ideas 16.6% first cycle, the second cycle 25%, 33.3% the third cycle; 3. Answering the questions: 25% the first cycle, the second cycle 33.3%, 41.6% the third cycle; 4. Discussion activity: the first cycle 33.3%, the second cycle 50%, 66.6% the third cycle; 5. Doing the tasks given: first cycle 75%, the second cycle 83.3%, 91.6% third cycle.